NMDA receptor antagonist rodent models for cognition in schizophrenia and identification of novel drug treatments, an update. (November 2018) - Cadinu, Daniela; Grayson, Ben; Podda, Giovanni; Harte, Michael K.; Doostdar, Nazanin; Neill, Joanna C.
Abstract: Negative and cognitive deficit symptoms in schizophrenia remain an unmet clinical need. Improved understanding of the neuro- and psychopathology of cognitive dysfunction in the illness is urgently required to enhance the development of new improved therapeutic strategies. Careful validation of animal models that mimic the behaviour and pathology of complex psychiatric disorders is an essential step towards this goal. Non-competitive NMDAR ( N -Methyl-d -aspartate receptor) antagonists e.g. phencyclidine (PCP), ketamine and dizocilpine (MK-801) can effectively replicate certain aspects of negative and cognitive deficits associated with schizophrenia in animals. In 2010 we reviewed the effects of NMDAR antagonism in tests for domains of cognition affected in schizophrenia, social behaviour and neuropathology, and in 2014, in tests for negative symptoms. In this update, we evaluate the most recent pharmacological strategies for restoring cognition in schizophrenia using NMDAR antagonist models, published since our original review in 2010 (cited over 225 times, excluding self-citations). Tests reviewed are, novel object recognition for visual recognition memory, attentional set shifting for executive function, and operant tests incorporating recent touchscreen technology for a range of domains including working memory, problem solving and attention, all impaired in schizophrenia. Moreover, we include an update on parvalbumin (PV)-expressing GABAergic interneurons and review, for the first time, the effects of NMDAR antagonists on gamma oscillations, circuitry integral for effective cognition. Data summarized in this review strongly confirm the reliability and usefulness of NMDAR antagonist animal models for evaluating novel therapeutic candidates, and for improving our understanding of the pathophysiology of cognitive deficits in schizophrenia. This article is part of the Special Issue entitled 'Psychedelics: New Doors, Altered Perceptions'. Highlights: NMDAR antagonists impair cognition relevant for schizophrenia in rodent tests. New therapeutic targets for cognition are evaluated in these tests. Effects of NMDAR antagonists on neuropathology and gamma oscillations are reviewed. Evaluation of novel treatments on behaviour and pathophysiology is recommended. Evaluation of novel treatments in more than one animal model is recommended.